Electron microscopy analysis of astrocyte-synapse interactions shows altered dynamics in an Alzheimer’s disease mouse model - Kater, Mandy S. J.; Badia-Soteras, Aina; van Weering, Jan R. T.; Smit, August B.; Verheijen, Mark H. G. (Frontiers in Cellular Neuroscience, 2023)
Astrocyte-synapse bi-directional communication is required for neuronal development and synaptic plasticity. Astrocytes structurally interact with synapses using their distal processes also known as leaflets or perisynaptic astrocytic processes (PAPs). We recently showed that these PAPs are retracted from hippocampal synapses, and involved in the consolidation of fear memory. However, whether astrocytic synaptic coverage is affected when memory is impaired is unknown. Here, we describe in detail an electron microscopy method that makes use of a large number of 2D images to investigate structural astrocyte-synapse interaction in paraformaldehyde-fixed brain tissue of mice. In addition, we show that fear memory-induced synaptic activation reduces the interaction between the PAPs and the presynapse, but not the postsynapse, accompanied by retraction of the PAP tip from the synaptic cleft. Interestingly, this retraction is absent in the APP/PS1 mouse model of Alzheimer’s Disease, supporting the concept that alterations in astrocyte-synapse coverage contribute to memory processing.